Pengaruh Gaya Hidup dan Motivasi terhadap Keputusan Pembelian Konsumen Barang Bekas Pakai di Pasar Kayu Jati Kota Tembilahan Kabupaten Indragiri Hilir - Agus Saputra, Irham; Mardiah, Ainun (Policy, Law and Political Research Center, 2024)
This research was conducted at Kayu Jati Market, Tembilahan City, Indragiri Hilir Regency, to analyze the influence of lifestyle and motivation on consumer purchasing decisions for used goods. This study also aims to determine the simultaneous impact of lifestyle and motivation on consumer purchasing decisions. The research population consists of people in Tembilahan City aged 18-50 years who have used or bought used goods. The research sample was selected using a purposive sampling technique, with a sample size of 100 respondents. The data were analyzed quantitatively using multiple linear regression with the help of the SPSS version 25 program. The results showed that lifestyle positively influences purchasing decisions and motivation, which has a positive effect on buying decisions. Simultaneously, lifestyle and motivation significantly influence purchasing decisions for used goods at Kayu Jati Market, Tembilahan City, Indragiri Hilir Regency.